Hydroxyethyl substituted linear polyethylenimine for safe and efficient delivery of siRNA therapeutics. Issue 62 (16th October 2018) - Patil, Sushilkumar; Lalani, Rohan; Bhatt, Priyanka; Vhora, Imran; Patel, Vivek; Patel, Hinal; Misra, Ambikanandan
Abstract : Hydroxyethyl substitution of linear polyethylenimine (LPEI) and its effects on physico-chemical and biological properties of polymer. Abstract : Linear polyethylenimine (LPEI) has been well reported as a carrier for siRNA delivery. However, its applications are limited due to its highly ionized state at physiologic pH and the resultant charge mediated toxicity. The presence of ionizable secondary amines in LPE are responsible for its unique characteristics such as pH dependent solubility and positive charge. Therefore, modification of LPEI was carried out to obtain hydroxyethyl substituted LPEI with the degree of substitution ranging from 15% to 45%. The impact of modification on the physicochemical parameters of the polymer, i.e. buffer capacity, solubility, biocompatibility and stability, was evaluated. Surprisingly, despite the loss of ionizable amines, the substitution improved solubility, and even overcame the pH dependent solubility of LPEI. In addition, the conversion of secondary amines to less basic tertiary amines after substitution improved the buffer capacity, in the endosomal pH range, required for efficient endosomal escape. It also reduced erythrocyte aggregation, hemolytic potential and in vitro cytotoxicity. The in vitro studies showed enhanced cell uptake and mRNA knockdown efficiency. Thus, the proposed modification shows a simple approach to overcome the limitation of LPEI for siRNA delivery.